Pengukuran Keterampilan Proses Sains dan Self-Efficacy Mahasiswa pada Matakuliah Mikrobiologi - Rukiah Lubis; Apriza Fitriani; Meti Herlina (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2022)
This study aims to describe students' initial science process skills and self-efficacy in Microbiology courses. The method used is the descriptive method. The data in this study were obtained through observation sheet instruments on science process skills and questionnaires related to self-efficacy. The measured science process skills indicators included 10 indicators: observing, classifying, finding conclusions, predicting, communicating, hypothesizing, planning experiments, manipulating materials and equipment, and applying and raising questions. The self-efficacy indicators studied are magnitude, strength and generality. The results showed that the average score of students' initial science process skill abilities was 67.2, while the student's initial self-efficacy score was 78. In conclusion, the initial science process skills ability of students in microbiology courses was in the less category, while Initial self-efficacy students are in the sufficient category. Keywords: Science Process Skills, Microbiology, Self-Efficacy